RESOURCE ASSESSMENT FEATURES OF NON-TRADITIONAL RESERVOIRS BY THE WELL-LOGGING DATA - Karpenko О.; Mikhailov, V.; Karpenko, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Possibilities of estimation of shale gas resource and gas of tight reservoirs with the use of the well-logging data on the example of typical gascondensate field in the southern side of the Dnieper-Donetsk Depression are considered. The peculiarity of such works at this stage of studying the prospects of unconventional hydrocarbon resources in Ukraine is the shortage of factual material regarding special geochemical analysis of the core from perspective intervals of well sections. Emphasis is placed on the application of data from the standard set of well-logging methods. Using the method of Q. Passy, the content of organic carbon (TOC) in the rocks within the intervals of drilled wells was estimated. The characteristics of the lithological composition of rocks and the gas saturation of the traditional type of reservoirs were taken into account in the well-logging data. In the absence of available core data on thermal maturity of the rocks within the identified promising thicknesses, gas resources were estimated in several scenarios. The peculiarities of the well-logging data interpretation in the case of cross sections of wells of gas-saturated rocks with capacitance characteristics below the limit are given. Dependencies of the type "porosity - permeability", "porosity - residual water saturation" should be used to establish a lower porosity and gas saturation limit for tight reservoirs. At the end of the article, recommendations for calculating of gas resources in non-conventional reservoirs are provided.